THE EFFECTIVENESS OF USING MIND MAPPING TECHNIQUE IN IMPROVING STUDENTS’ WRITING SKILL - Tiyas Salviyati; Sudarkam R Mertosono; Rofiqoh Rofiqoh (e-Journal of ELTS (English Language Teaching Society), 2022)
The objective of this research is to find out if using mind mapping technique is effective in improving writing skill of grade nine students of SMP Negeri 14 Palu. This research used pre-experimental research design. The sample of this research included 25 students of grade IX Cempaka who were selected by using purposive sampling technique. The instrument of data collection was an essay test that was divided into pre-test and post-test. The results of the data analysis showed that there was a significant difference between the result of the pre-test and the post-test. It indicates by the mean score of both tests results where the mean score of the experimental class significantly increased from 68.27 to 74.93. Based on the result of pre-test and post-test, the researchers found that the value of t-counted is 6.54. By applying a degree of freedom (df) 24 (25-1) and 0.05 level of significance, the researchers found that the value of t-table is 1.711 which showed that the value of t-counted was higher than t-table. It means that the use of mind mapping technique is effective in improving students’ writing skill of grade nine students of SMP Negeri 14 Palu. The implication of this finding is that mind mapping technique can be used in teaching and learning English especially in writing skill.